Phytochemical Analysis and Thin Layer Chromatography Profiling of Crude Extracts from Senna Occidentalis(Leaves) - Lawal, A. M.; Abdullahi, R.; Ibrahim, M. S.; Kurfi, M. Y.; Khalid, A.; Nuhu, M. (Journal of Biotechnology and Biomedical Science, 2019)
Plants used for medicinal practices which were discovered since prehistoric stone ages are termed Medicinal plants, which are also referred to as medicinal herbs, since plants produces bioactive chemical compounds (phytochemicals), this research however, is concerned with the extraction using Soxhlet extraction technique, phytochemical screening using various test methods, which reveals the presence of anthraquinones (free anthraquinones and combined anthraquinones), carbohydrates, cardiac glycosides, glycosides, flavonoids, saponins, steroids/ terpenes, phenolic compounds and tannins, and absence of alkaloids for extracts of senna occidentalis and also, thin layer chromatography profiling which gives probable foundation for further structural elucidation amongst others. This research shows the presence of potent secondary metabolites present in the leaves of senna occidentalis (leaves).
Keywords: Medicinal herbs; Medicinal plants; Phytochemicals; Drug Development; Chromatography.